Estudo comparativo de estratégias de controle aplicadas a um gerador síncrono - Jacome, Isac Calistrato (2012)
The robustness and performance of the Variable Structure Adaptive Pole Placement Controller are evaluated in this work, where this controller is applied to control a synchronous generator connected to an infinite bus. The evaluation of the robustness of this controller will be accomplished through simulations, where the control algorithm was subjected to adverse conditions, such as: disturbances, parametric variations and unmodeled dynamic. It was also made a comparison of this control strategy with another one, using classic controllers. In the simulations, it is used a coupled model of the synchronous generator which variables have a high degree of coupling, in other words, if there is a change in the input variables of the generator, it will change all outputs simultaneously. The simulation results show which control strategy performs better and is more robust to disturbances, parametric variations and unmodeled dynamics for the control of Synchronous Generator